Between Laughter and Identity Challenges: The Dark Jokes Phenomenon and Its Role in Social Space - M Fikran Pandya; Nurul Shofiah; Novia Sholichah; Iqbal Ali Wafa; Emrah Ekmekçi (Tazkiya Journal of Psychology, 2026)
Originally restricted to select comedy club circuits, dark jokes gradually transcended their insularboundaries, permeating broader public domains and mass media platform. This study aims to in-depth examine students' attitudes and perceptions toward the phenomenon of dark jokes using a descriptive qualitative approach. Data were collected through an online questionnaire involving 24 psychology students aged 18–22, divided into two groups: 14 students from Islamic boarding schools (pesantren) and 10 students from non-Islamic boarding schools (pesantren). Thematic analysis yielded three main themes. First, dark jokes are perceived as a humor orientation that falls on the spectrum between normality and ethical violations. Second, the acceptance of dark jokes is largely determined by social context, such as interaction space, generational affiliation, and age similarity. Third, the practice of dark jokes becomes part of self-presentation in society, reflecting not only the content of the joke but also the identity of the listener. These findings demonstrate the potential of dark jokes as a marker of social identity, containing opportunities for building group solidarity as well as challenges in the form of potential social conflict. This study highlights the importance of local context in understanding controversial humor and recommends optimizing social media as a safe space for expression. Further studies with in-depth interviews are needed to explore the psychological and sociocultural dynamics more comprehensively.